INTEGRATING LOCAL WISDOM- BASED SCIENTIFIC APPROACH ON CHEMISTRY LEARNING AT FIRST GRADE OF SMAN 1 PURWOREJO TO IMPROVE LEARNING DISCIPLINE - Sulistiana Febriawati; Jaslin Ikhsan (Universitas Negeri Yogyakarta, 2016)
Indonesian government supported the integration of local wisdom into education. It was proven by the existence of the Act No. 20/2003 on National Education System and the Regulation of the minister of Education and Culture No. 81A/2013. Local wisdoms of Purworejo could be matched into chemistry learning. This research was to measure the difference of learning discipline at SMAN 1 Purworejo between students who learnt chemistry by integrating local wisdom-based scientific approach and those who were without the integration of local wisdom. There were a control class and treatment class in this study. Before getting the treatments, the students fulfilled the questionnaire as the prior learning discipline. The treatments experienced by the students were chemistry experiment, presentation, essay writing, and the discussion in traditional organization on chemistry learning. After joining the treatments, the students fulfilled the final questionnaire. Data were analyzed by using Independent Sample t-Test of SPSS from which learning discipline of students at the treatment class was significantly different from those who were at the control class (Sig.p 0.000). This research inferred that learning discipline of students who studied by the use of local wisdom -based scientific approach was significantly different from that were without the integration of local wisdom.